2015
DOI: 10.1007/s00436-015-4660-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection and identification of four major Schistosoma species by high-resolution melt (HRM) analysis

Abstract: Schistosomiasis, caused by blood flukes belonging to several species of the genus Schistosoma, is a serious and widespread parasitic disease. Accurate and rapid differentiation of these etiological agents of animal and human schistosomiasis to species level can be difficult. We report a real-time PCR assay coupled with a high-resolution melt (HRM) assay targeting a portion of the nuclear 18S rDNA to detect, identify, and distinguish between four major blood fluke species (Schistosoma japonicum, Schistosoma man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The dye fluoresces strongly when intercalated into the double-stranded DNA, but as the temperature increases during the HRM analysis, the DNA melts and the dye is release without fluorescence. The changes in fluorescence are sequence specific and can be recorded and analyzed by the designed program (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The dye fluoresces strongly when intercalated into the double-stranded DNA, but as the temperature increases during the HRM analysis, the DNA melts and the dye is release without fluorescence. The changes in fluorescence are sequence specific and can be recorded and analyzed by the designed program (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The research conducted in the Philippines also showed similar trends, demonstrating that traditional copro-parasitological techniques underestimate the infection rate, signifying the advantages of qPCR for case finding and disease surveillance and monitoring [ 87 , 88 , 89 , 90 , 91 ]. Besides the gene of NADH I [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ], several qPCR methods have been established targeting other genes, including COX I [ 96 ], 18S rRNA [ 97 , 98 , 99 , 100 , 101 ], ITS 2 [ 102 ], SjR2 [ 99 , 103 , 104 ], SjCHGCS20 [ 22 ], SjCHGC08270 [ 20 , 105 ], and Sjrh1.0 [ 99 , 106 ] ( Table 2 ). Those established qPCR methods have mostly completed the laboratory evaluation, but further validation should be conducted in field settings.…”
Section: Molecular Methods Developed To Detect the Pathogen Of Schist...mentioning
confidence: 99%
“…The experiment was performed in triplicate in a final volume of 15 µl by mixing 2 µl of first-strand cDNA with 1× iTaq Universal SYBR Green master mix (Bio-Rad Laboratories Inc., Hercules, CA, USA) and 100 nM each of Fw and Rv primers (Additional file 1: Table S1). 18S RNA was used as an internal control, as described previously [42, 43]. Amplification was performed using the MasterCycler Real-Time PCR system (Realplex 4 , Eppendorf, Hamburg, Germany) with pre-incubation at 95 °C for 5 min, followed by 40 cycles of 95 °C for 15 s and 60 °C for 1 min.…”
Section: Methodsmentioning
confidence: 99%